NEEDS ANALYSIS FOR DEVELOPING ICT-BASED INTERACTIVE E-MODULES ON FLIP HEYZINE IN ENGLISH LANGUAGE LEARNING IN ELEMENTARY SCHOOL - Qurota A'Yunin; Sabariah; Harwanto (Universitas Negeri Surabaya, 2026)
Due to conventional teaching materials that do not match the digital conveniences of learners and the demand of the Kurikulum Merdeka framework, English language learning in Indonesian elementary schools faces persistent challenges. This current study was carried out to analyze the needs as preliminary step for developing ICT-based interactive e-modules through Flip Heyzine in learning English. It used descriptive qualitative design with research subjects that is English teacher of 5 elementary schools and students grade IV-VI numbering 30people. Questionnaires were distributed, semi-structured interviews were conducted, and ten sessions of classroom observation were held; the data collected were analyzed using descriptive statistics and thematic analysis. The results reveal four major areas of need: the existing quality of traditional pedagogical content is insufficient, students have a significant lean towards using digital and interactive study materials despite teachers having positive attitudes toward ICT adoption but only moderate levels of competency with it, teachers had sufficient access to personal smartphone and mobile data to support Heyzine's browser-based share-link deployment model. Flip Heyzine has full support for all the high priorities features requested by participants; that is somewhat confusing as they used embedded audio, instructional video, interactive quizzes and child friendly visual design. The findings provided strong empirical groundwork for the subsequent construction of Heyzine-based interactive e-modules and also suggested areas for future studies, including expert validation and effectiveness testing within a real-life elementary English learning environment.